Assessment of Students' Absorption of Printed Graphic Design Material Using the Blended Learning Model - Audina, Nurul (Jurnal Guru Komputer, 2021)
This research is motivated by the problems that researchers encountered in the field, namely the student absorption of Printed Graphic Design, is still lacking. Therefore, there is a need for a learning model that can help improve students understanding of the material combining vector-based image and text. One of the alternatives used by researchers to overcome this problem during the Covid-19 period is by using a blended learning model. This study aims to prove the doubts about student’ understanding ability of Printed Graphic Design materials. To achieve good results participants used the class action research method from Kurt Lewin, which states that in one cycle there are four main steps, namely (1) planning, (2) action, (3) observation, (4) reflection. The learning outcomes of the first cycle were not in line with expectations because students who scored ≥ 75 is only 22.86%, while the expected value if students who scored ≥ 75 had achieved completeness ≥ 75%. Meanwhile in cycle II, there is an increase in learning outcomes where the results are in accordance with expectations because students who score ≥ 75 are more than 75% of the total number of students, which is 100%.